Growth, Convergence and EU Membership - Jesus Crespo Cuaresma; Maria Antoinette Dimitz; Doris Ritzberger-Grünwald (Oesterreichische Nationalbank (OeNB), 2002)
The effect of European integration on long-term growth of the current EU member states is studied by means of panel data methods. The length of EU membership is found to have a significant positive effect on economic growth, which is relatively higher for poorer countries. The existence of a growth bonus from EU membership appears inconsistent with neoclassical exogenous growth theory. While previous empirical studies tend not to find positive growth effects of regional integration, the present study suggests an asymmetric, convergence-stimulating impact of EU membership on long-term growth.
Keywords: F15; F43; C23; 330; Convergence; Economic Growth; European Union; Threshold panel data regression